A study on the Cost and Return at different levels of milk production per Cow - Basumatary, Priyo; Zaman, Aminuz; Bhujel, Anand Kumar (The journal of contemporary issues in business and government, 2021)
The cost and return on milk production is an important consideration for the dairy farmers to continue the activities of dairy farming. The study is undertaken with the objective of ascertaining the cost and return on production of milk at different levels of production. To conduct this study the researcher has obtained primary data from 40 dairy farms in Kamrup metro and Morigaon districts. The result shows that the dairy farmer garners higher return on direct sale to customers and hotels. There is an economies of scale in fodder and labour cost incurred for the dairy farmers rearing maximum number of cows with higher productivity. The increasing cost of feeds and fodder and lack of skilled manpower is a major constraint for the dairy farmers to continue dairy farming activities.